Pemberdayaan dan Peningkatan Ekonomi Melalui Pelatihan Pembuatan Berbagai Produk dari Bahan Dasar Pisang di Desa Paya Cut Kecamatan Juli Kabupaten Bireuen - Marzalina, Marzalina; Muttaqim, Hakim; Gustami, Heri; Meilinar, Fina; Pratama Putra, Dani (LPPM Umuslim, 2024)
This community service program aims to improve the economy of the people of Desa Paya Cut, Kecamatan Juli, Kabupaten Bireuen, through training in the production of processed banana products. Desa Paya Cut has abundant natural resources in the form of bananas, but their utilization to increase community income is still not optimal. This training will cover various types of processed banana products, such as banana chips, banana dodol, and banana cakes, as well as packaging, storage, and marketing techniques. It is expected that this program can improve the skills of the community in processing bananas, increase the sales of processed banana products, and raise community awareness of the potential of bananas as a source of income